DAMPAK PENGUMUMAN PENERBITAN OBLIGASI PERUSAHAAN TERHADAP ABNORMAL RETURN SAHAM DI INDONESIA TAHUN 2014 – 2015 - Rathria Arrina Rachman; Dahlia Ervina (MIX: JURNAL ILMIAH MANAJEMEN, 2017)
Abstract. This study aims at investigating the effect of corporate bonds issuanceannouncement on the stock market in Indonesia over 2014 – 2015. By applying eventstudy and t-test, it is proven that there are significant positive abnormal return one daybefore the announcement date and significant negative abnormal return five days afterthe date. This result shows that public has obtained information from the insider asgood news before the information is widely disseminated; therefore, they react bytransacting in the stock market. Nonetheless, when the offering period ends, marketparticipants react again and there is a market correction five days after theannouncement. This result confirms that there is a signalling effect of corporate bondsissuance on the stock market performance and indicates that stock market in Indonesiais inefficient.